Political Dynasties in the Government System in Indonesia - Danny Permana (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
There are many phenomena where politicians try to perpetuate their power through political dynasties, especially in local government. This is worrying, considering that the abuse of power will be easier with the political elite consisting of their own families. This research will then look at how political dynasties can occur in the Indonesian government system. This research will be carried out using a descriptive qualitative approach. The data used in this research was obtained through the literature study method. The results of this research then found that several factors cause political dynasties to occur in Indonesia. The first factor is Indonesian society which is plural, so individual political behavior is strongly influenced by social, economic, psychological, historical, political, and cultural factors. Another factor is that candidates who have charisma and popularity will provide great opportunities and make it easier for other family members to run for office in society.